1994
DOI: 10.1002/qua.560520504
|View full text |Cite
|
Sign up to set email alerts
|

Quantum mechanical valence study of a bond‐breaking–bond‐forming process in triatomic systems

Abstract: The recently introduced set of the quadratic, two-electron covalent and ionic valence indices is used to investigate the bond-breaking-bond-forming (BB-BF) process in an atom exchange reaction between H2 and X (X = H, F-I) as well as in the 0 2 -H system. Valence changes accompanying selected charge reorganizations are examined within the three-orbital model and valence diagrams for symmetric transition states (TSS) are given. The UHF valence data for Liz0 and C02 and the H-H-X, 0-0-H, and 0-H-0 (ABC) TSS (col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 103 publications
(73 citation statements)
references
References 25 publications
(17 reference statements)
3
70
0
Order By: Relevance
“…The NOCV have been derived from the NalewajskiMrozek valence theory [40][41][42][43][44][45] as eigenvectors that diagonalize the deformation density matrix. It was shown that the pairs of the natural orbitals for chemical valence (w -k , w k , corresponding to eigenvalues -v k and v k ) decompose the differential density Dq into NOCV-contributions (Dq k ):…”
Section: Computational Details and Modelsmentioning
confidence: 99%
“…The NOCV have been derived from the NalewajskiMrozek valence theory [40][41][42][43][44][45] as eigenvectors that diagonalize the deformation density matrix. It was shown that the pairs of the natural orbitals for chemical valence (w -k , w k , corresponding to eigenvalues -v k and v k ) decompose the differential density Dq into NOCV-contributions (Dq k ):…”
Section: Computational Details and Modelsmentioning
confidence: 99%
“…A similar description follows [1][2][3] from the Wiberg-type bond-multiplicities formulated in the MO theory [4,[14][15][16][17][18][19][20][21][22][23]. In MO description the chemical interaction between, say, two (valence) AO or general basis functions originating from different atoms is strongly influenced by their direct overlap and interaction, which both condition the bonding effect experienced by electrons occupying their bonding combination in the molecule, compared to the non-bonding reference of electrons on separated AO.…”
Section: R F Nalewajski (B)mentioning
confidence: 99%
“…It vanishes for the lone-pair configurations, when P = (0 or 1), This simple model thus properly accounts for the competition between the bond covalency and ionicity, while preserving the single bond-order measure reflected by the conserved single IT multiplicity of the chemical bond. Similar effects transpire from the quadratic bond indices formulated in the MO theory [87][88][89][90][91][92][93][94][95][96][97]. For example, the plot of Wiberg bond-order [87] for this model (see Fig.…”
Section: Illustrative Example: Two-orbital Model Of Chemical Bondmentioning
confidence: 62%
“…= S, i.e., the overall conditional entropy of the average AO channel in the CI MO-ensemble [Eq. (93)], now stands for the overall entropic measure of the bond multiplicity.…”
Section: Illustrative Example: Two-orbital Model Of Chemical Bondmentioning
confidence: 99%